Is adult attachment associated with engagement with services? A systematic literature review. (3rd September 2021) - McGonagle, G.; Bucci, S.; Varese, F.; Raphael, J.; Berry, K.
Abstract: Background: People with psychosis often experience difficulties engaging in mental health treatments. Aims: This review sought to identify, summarise and critically evaluate studies that investigated associations between adult attachment and relationships with mental health services in the context of psychosis. Method: A search was conducted on the following databases from 1980 to February 2019: Web of Science; PubMed; CINAHL; and PsycINFO. Of the 10, 683 articles identified, 11 met inclusion criteria for the review. These articles were then quality appraised using the Effective Public Health Practice Project tool (EPHPP). Results: There was some evidence of associations between insecure attachment (namely avoidant attachment) and therapeutic alliance, and insecure attachment and engagement with services. Secure attachment was also associated with self-reported attachment to services as a whole. There were a number of limitations across the studies; the majority of studies were cross-sectional and it was difficult to make comparisons between studies due to the range of different measures used to assess attachment and alliance. Conclusion: Adult attachment security may be an important factor to consider in determining the way in which service users with psychosis engage with mental health services.